MORAL INJURY EXPERIENCES IN PEER SUPPORT OF ODHA SURVIVORS: BETWEEN CONCERN AND MORAL CONFLICT - Roro Setyawati; Mohd Nazri Abdul Rahman; Mahdi Anbari; Endah Silawati; Anggi Safitri (SOSIOEDUKASI, 2026)
This study examined experiences of moral injury among peer supporters who are also people living with HIV/AIDS (PLWHA). A qualitative phenomenological design was employed using Interpretative Phenomenological Analysis (IPA). Six PLWHA peer supporters in Banyumas, Central Java, participated in semi-structured interviews. Data were analyzed thematically.The findings identified two forms of moral injury. Perpetration-based moral injury was characterized by guilt, shame, and self-disgust associated with the internalization of stigma related to HIV status and sexual orientation. Betrayal-based moral injury emerged from perceived betrayal by the healthcare system, intimate partners, and family members, as well as value conflicts encountered during peer support practice. Despite these experiences, participants engaged in processes of moral repair, including social support from Peer Support Groups, self-acceptance, increased self-awareness, meaning-making, and a commitment to helping others. The findings indicate that PLWHA peer supporters experience multifaceted moral injury while also demonstrating transformative resilience. These results underscore the importance of integrative interventions that address moral injury and facilitate moral repair through strengthening social support systems and enhancing individual resilience.